(untitled) (Jurnal Pembangunan Sosial, 2011)
Population aging is a 21 st century phenomenon. The population aging occurs as the proportion of older people relative to younger group increases. This process has creating various problems not only for developed countries but also developing countries. The population of Indonesia also has shown signs of aging. As age of the population increases, and many people are living longer, there will be many more elderly in the society. This article discusses the population aging in Indonesia and discusses the problems resulting from the population aging.